The effect of work motivation and employee engagement on employee job satisfaction - Taruna, Indra; Nisa, Azka Aulian (Jurnal Mantik, 2024)
Increasing job satisfaction is important for companies because it has a positive impact such as improving employee performance, loyalty, and productivity. In this study, it will be discussed how work motivation and employee engagement affect the job satisfaction of Perumdam Tirta Kerja Raharja employees. The independent variables tested were work motivation and employee engagement while job satisfaction was the dependent variable. The research method used in this study is quantitative. The population in this study were employees at Perumdam Tirta Kerja Raharja. The sampling technique used in this study was purposive sampling and the magnitude of the sample in this study was calculated by the Slovin formula, so the total number is 90 respondents. The analysis method used in this study is several multiple linear regression analyses using SPSS 25 for Windows. The results of this study show that work motivation and employee engagement affect the job satisfaction of Perumdam Tirta Kerja Raharja employees. The magnitude of the influence of work motivation and employee engagement on employee job satisfaction was 53.1%.